2004
DOI: 10.1142/s0218348x04002549
|View full text |Cite
|
Sign up to set email alerts
|

Self-Similar Space-Filling Packings in Three Dimensions

Abstract: We develop an algorithm to construct new self-similar space-filling packings of spheres. Each topologically different configuration is characterized by its own fractal dimension. We also find the first bicromatic packing known up to now.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
22
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 9 publications
(19 reference statements)
2
22
0
2
Order By: Relevance
“…The signicantly steeper power-law slope in this region (q À2.7 ) is close to what would be expected for close-packed spheres. 44 The persistence of the mass fractal scattering to q-values close to q max suggests that the fractal clusters grow self-similarly as gelation proceeds, unlike the low-f case where the fractal scaling changes continually throughout the gel transition.…”
mentioning
confidence: 98%
“…The signicantly steeper power-law slope in this region (q À2.7 ) is close to what would be expected for close-packed spheres. 44 The persistence of the mass fractal scattering to q-values close to q max suggests that the fractal clusters grow self-similarly as gelation proceeds, unlike the low-f case where the fractal scaling changes continually throughout the gel transition.…”
mentioning
confidence: 98%
“…Details on the construction algorithm and on the complete set of new configurations will be published elsewhere [8]. We give here only a qualitative description of this technique for the bichromatic packing.…”
mentioning
confidence: 99%
“…Here, we show that for all the self-similar spacefilling packings constructed by inversive geometry of Refs. [19,[28][29][30][31], cuts along random hyperplanes generally have a fractal dimension of the one of the uncut packing minus one, what we prove analytically. Nevertheless, these packings are still heterogeneous fractals since cuts along special hyperplanes of a single packing show specific fractal dimensions.…”
Section: Introductionmentioning
confidence: 66%
“…1, which are generated using inversive geometry as in Refs. [19,[28][29][30][31] and which therefore are exactly self-similar. Reference [30] previously showed that the packing in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation